2021
DOI: 10.1039/d1rp00037c
|View full text |Cite
|
Sign up to set email alerts
|

Location-thinking, value-thinking, and graphical forms: combining analytical frameworks to analyze inferences made by students when interpreting the points and trends on a reaction coordinate diagram

Abstract: Reaction coordinate diagrams (RCDs) are chemical representations widely employed to visualize the thermodynamic and kinetic parameters associated with reactions. Previous research has demonstrated a host of misconceptions students adopt when...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Specifically, students who reasoned based on the number of steps demonstrated focus on a representational surface feature that could be drawn from either the RCD or EPF. Students' writing that appealed to the surface features of the representations aligns with prior studies indicating students' reliance on surface features for both RCDs (Lamichhane et al, 2018;Popova and Bretz, 2018a, 2018b, 2018cParobek et al, 2021) and the EPF (Strickland et al, 2010;Anzovino and Bretz, 2015;Galloway et al, 2017;Graulich and Bhattacharyya, 2017;Caspari et al, 2018;Dood et al, 2020;Watts et al, 2020). Students' reliance on representational surface features is valuable to identify, as a key component of developing representational competence is being able to interpret the chemical meaning of representations when supporting their reasoning (Kozma and Russell, 2005).…”
Section: Students Who Selected Mechanism a As Most Likely Reasoned By...supporting
confidence: 68%
See 1 more Smart Citation
“…Specifically, students who reasoned based on the number of steps demonstrated focus on a representational surface feature that could be drawn from either the RCD or EPF. Students' writing that appealed to the surface features of the representations aligns with prior studies indicating students' reliance on surface features for both RCDs (Lamichhane et al, 2018;Popova and Bretz, 2018a, 2018b, 2018cParobek et al, 2021) and the EPF (Strickland et al, 2010;Anzovino and Bretz, 2015;Galloway et al, 2017;Graulich and Bhattacharyya, 2017;Caspari et al, 2018;Dood et al, 2020;Watts et al, 2020). Students' reliance on representational surface features is valuable to identify, as a key component of developing representational competence is being able to interpret the chemical meaning of representations when supporting their reasoning (Kozma and Russell, 2005).…”
Section: Students Who Selected Mechanism a As Most Likely Reasoned By...supporting
confidence: 68%
“…Hence, their findings suggest the need to provide students with further opportunities to develop their reasoning with RCDs. Furthermore, across the articles describing students' interpretations of RCD surface features, researchers identified that students often conflate transition states with intermediates, do not note energy changes encoded on the y-axis, and view the x-axis as corresponding to time (Lamichhane et al, 2018;Popova and Bretz, 2018c;Parobek et al, 2021). The findings regarding students' understandings of RCD surface features and how they connect to mechanisms suggest a need to further support students' use and understanding of RCDs within the organic chemistry curriculum.…”
Section: Reasoning With Mechanistic Representations In Organic Chemistrymentioning
confidence: 99%
“…Representational competence refers to ''a set of skills and practices that allow a person to reflectively use a variety of representations or visualizations, singly and together, to think about, communicate, and act on chemical phenomena in terms of underlying, aperceptual physical entities and processes'' (Kozma and Russell, 2005, p. 131). Representational competence has frequently been of interest in chemistry education research (Atkinson et al, 2021;Parobek et al, 2021;Popova and Jones, 2021;To ´thova ´et al, 2021;Watts et al, 2022) and has been considered when evaluating the effect of representations on students' learning (Larkin and Simon, 1987;Hsu and Yang, 2007;Ariasi and Mason, 2014;Enero Upahi and Ramnarain, 2019;Gkitzia et al, 2020).…”
Section: Non-textual Explanationsmentioning
confidence: 99%
“…Diagrams relating changes in energy to reaction coordinates have been conceptually important to both research and teaching for over 50 years. They are central to many organic chemistry curricula and have been identified as anchoring concepts in chemical education. , The way they are taught and understood by students has been examined in detail from several perspectives. …”
Section: Introductionmentioning
confidence: 99%